1993
DOI: 10.1259/0007-1285-66-788-667
|View full text |Cite
|
Sign up to set email alerts
|

Sedation and patient monitoring in vascular and interventional radiology

Abstract: A postal survey of British and Irish interventional radiologists was carried out in 1991 in order to assess current practice with respect to sedation and monitoring of patients during angiography and interventional procedures. The response rate was 65%. 49% of patients are fasted prior to angiography and 68% prior to interventional procedures. Radiologists participate in obtaining consent in 60% of cases. Patients are often (50%) sedated for angiography and usually (62-94% depending on the procedure) sedated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 4 publications
0
10
0
2
Order By: Relevance
“…While a small literature exists regarding standard sedation practices for elective interventional radiology procedures of various types (McDermott et al, 1993; Mueller et al, 1997), emergent acute stroke therapy is distinct. Single center case series of non-emergent procedures showed no apparent increase in complication rates in neurointerventional procedures performed in awake patients (Qureshi et al, 2001; Abou-Chebl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…While a small literature exists regarding standard sedation practices for elective interventional radiology procedures of various types (McDermott et al, 1993; Mueller et al, 1997), emergent acute stroke therapy is distinct. Single center case series of non-emergent procedures showed no apparent increase in complication rates in neurointerventional procedures performed in awake patients (Qureshi et al, 2001; Abou-Chebl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Die groûe Mehrzahl der Eingriffe unter Sedation wird von den minimalinvasiv tätigen ¾rzten selbst durchgeführt. Nach Literaturangaben ist nur in etwa 10 % der Fälle bei radiologisch-interventionellen Eingriffen ein Anästhesist vor Ort, in den meisten Fällen allerdings eine hierfür ausgebildete Pflegekraft [3]. Zielsetzung der Analgosedierung ist es, minimalinvasive Eingriffe möglichst schmerz-und angstfrei für den Patienten zu gestalten, wobei im Gegensatz zur Allgemeinnarkose die Schutzreflexe und die Kooperationsfähigkeit erhalten bleiben.…”
Section: Abstract Sedation´sedoanalgesia´pain Control´interventionalunclassified
“…In der Vergangenheit reichte dies von Lachgas als Maskennarkose [7,8], bis hin zur intravenösen Gabe von Nalbuphin (Nubain ), Pentazocin (Fortral ), Morphin (u. a. MST , MSR ) [3,9], Diazepam (u. a. Valium , Tranquase ) [10] oder Tramadol (Tramal ) [11]. In neuerer Zeit wurden besonders Midazolam (Dormicum ) oder Propofol (u. a. Disoprivan , Klimofol ) als Einzelmedikation eingesetzt [12 ± 14].…”
Section: Abstract Sedation´sedoanalgesia´pain Control´interventionalunclassified
“…For example, surveys undertaken in Europe, 1 the United States, 2 and the United Kingdom 3 have identified a variety of conscious sedation protocols involving the use of an assortment of benzodiazepine, analgesic, and antihistamine medications that aim to keep patients in an awake/alert state of consciousness during radiologic diagnostic or interventional procedures. Moreover, when comparing the degree and use of sedation in diagnostic and interventional vascular and visceral procedures, Haslam et al 1 found that, in general, interventional visceral procedures were performed using deeper levels of sedation.…”
mentioning
confidence: 99%